Arduino Based System Design for Measuring Heart Rate and Body Temperature - Adnan M.A SHAKARJI; Adem GÖLCÜK (International Journal of Applied Methods in Electronics and Computers, 2022)
The aim of this study is to develop a multi-sensor and low-cost biosensor system using Arduino Uno microcontroller board. With this system, heart rate and body temperature can be measured digitally. In this way, the vital values of those with health problems will be monitored regularly, and sudden changes in vital values will be detected immediately. While developing the system, Arduino Uno control card, heart rate sensor and temperature sensor were used. In addition, a software sensitive to detecting changes in heart rate and body temperature has been developed. The system created is open to future additions and improvements. The data obtained through the sensors on the system can be easily tracked by transferring them to the computer over wi-fi. At the same time, it can be improved by placing more sensors in the system according to the purpose of use. As a result of the tests, it has been seen that the system successfully transmits the information received from the sensors to the users in the desired time and gives an audible warning at the determined critical values. Thanks to this system, vital changes in heart rate and body temperature can be accessed remotely and instantly, and it is thought that this will contribute to the field of medicine.